2015
DOI: 10.15252/embr.201540467
|View full text |Cite
|
Sign up to set email alerts
|

Selective influence of Sox2 on POU transcription factor binding in embryonic and neural stem cells

Abstract: Embryonic stem cell (ESC) identity is orchestrated by co-operativity between the transcription factors (TFs) Sox2 and the class V POU-TF Oct4 at composite Sox/Oct motifs. Neural stem cells (NSCs) lack Oct4 but express Sox2 and class III POU-TFs Oct6, Brn1 and Brn2. This raises the question of how Sox2 interacts with POU-TFs to transcriptionally specify ESCs versus NSCs. Here, we show that Oct4 alone binds the Sox/Oct motif and the octamer-containing palindromic MORE equally well. Sox2 binding selectively incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 57 publications
(100 reference statements)
2
76
0
Order By: Relevance
“…In addition, any multimers of GFP-Oct4 were also not detected. These results indicate that heterodimer complexes are only possible in the presence of DNA which is in agreement with our previous work (Chen, Tapan et al 2012;Mistri, Devasia et al 2015).…”
Section: The Sox2-oct4 Protein-protein Interaction Requires Dna-havinsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, any multimers of GFP-Oct4 were also not detected. These results indicate that heterodimer complexes are only possible in the presence of DNA which is in agreement with our previous work (Chen, Tapan et al 2012;Mistri, Devasia et al 2015).…”
Section: The Sox2-oct4 Protein-protein Interaction Requires Dna-havinsupporting
confidence: 93%
“…Together these results add biochemical detail to our finding that fusion Oct4 and Sox2 were similar in their functionalities as like wild type Oct4 and Sox2. Taking into account the higher expression levels for the N-terminal fusion plasmid constructs, we further characterised GFP-Oct4 and mCherry-Sox2 for their physiological functional ability in rescuing ES cells in which the corresponding endogenous TF alleles had been deleted specifically during trophectodermal differentiation (Mistri, Devasia et al 2015).…”
Section: Characterization Of Tfs-fluorescent Fusion Proteins-to Enablmentioning
confidence: 99%
“…Neural POU proteins have previously been reported to form highly cooperative homodimers in vitro [48]. A recent study has shown that class III POU TFs preferentially target the MORE sequence in NPCs [49]. The authors used full-length proteins fused to large fluorescent tags to verify that Oct6 preferentially forms homodimers, whereas Sox2 preferentially heterodimerizes with Oct4 on SoxOct elements.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, OCT4 displayed two orders of magnitude fewer ChIP-seq peaks in NIH-3T3 as compared to ES cells (Liang et al, 2008). As SOX2 and OCT4 form heterodimers, and SOX2 can recruit OCT4 to DNA (Chen et al, 2014;Mistri et al, 2015), we reasoned that OCT4 may have a low intrinsic ability to find its target sites in the absence of a heterodimeric partner. To test this hypothesis, we co-expressed a YPet-SOX2 fusion protein with OCT4-HA in NIH-3T3 and performed ChIP-seq against OCT4.…”
Section: The Mbf Predicts Genome-wide Tf Occupancymentioning
confidence: 99%